Cobalt and copper pyridylmethylphosphonates with two- and three-dimensional structures and field-induced magnetic transitions. Issue 44 (21st October 2015) - Yang, Ting-Hai; Cai, Zhong-Sheng; Shi, Fa-Nian; Zheng, Li-Min
Abstract : Compounds [Co(4-pmp)] (1 ) and [Cu(4-pmp)(H2 O)] (2 ) (4-pmp = 4-pyridylmethylphosphonate) with 2-D and 3-D structures are synthesized and characterized, which show metamagnetism at low temperature. Abstract : Two novel metal pyridylmethylphosphonates, namely, [Co(4-pmp)] (1 ) and [Cu(4-pmp)(H2 O)] (2 ), (4-pmpH2 = 4-pyridylmethylphosphonic acid), have been hydrothermally synthesized and characterized by X-ray diffraction, infrared spectroscopy, elemental analysis, and thermogravimetric analysis. In compound1, each PO3 C tetrahedron is corner-shared with three CoNO3 tetrahedra and vice versa, thus forming a one-dimensional (1-D) inorganic chain along the a axis containing 8-membered rings of [(Co–O–P–O)2 ]. The inorganic chains are further connected by a 4-pmp 2− ligand, generating a 2-D layered structure. Compound2 displays a three-dimensional (3-D) framework structure, in which the inorganic layers are pillared by the pyridyl groups of the ligand, generating a 3-D pillared-layered structure. The magnetic properties of1 and2 have been studied. Compounds1 and2 behave as metamagnets at low temperature. The critical fields are about 70 kOe for1 and 47 kOe for2 at 1.8 K.